Towards a Best Practice for the Use of Active Non‐contact Surface Scanning to Record Human Skeletal Remains from Archaeological Contexts. (20th April 2017) - Errickson, D.; Grueso, I.; Griffith, S. J.; Setchell, J. M.; Thompson, T. J. U.; Thompson, C. E. L.; Gowland, R. L.
Abstract: Active surface scanners emit light or a laser stripe to record the exterior surface of an object or landscape, providing results in three dimensions. The use of active surface scanners to record anthropological and archaeological contexts has increased within the last few years, creating a number of sub‐contexts within these disciplines and allowing a further development of certain applications, such as quantitative analysis, the use of replicas in education and museums and the creation of digital databases archived in institutions. However, with guidance, this paper aims to assess the advantages and disadvantages of active surface scanning and the potential for research with regard to the recording and analysis of human skeletal remains. The key advantages and uses identified include quantitative digitisation, geometric morphometric studies, conservation, preservation, documentation and reconstruction. However, surface scanning also has some limitations, including cost, technological expertise, the need for a power source, computing requirements and data size. Overall, the application of active surface scanning technology to archaeological skeletal remains will provide a vital digital archive that will serve to preserve the integrity of this fragile and finite resource for future generations. This is particularly important within the current developer‐funded environment in which many skeletal collections, including those yielding unique or unusual pathological or morphological features, are re‐buried, with only very limited time for analysis. Copyright © 2017 John Wiley & Sons, Ltd.